A pilot study shows the positive effects of continuous airway pressure for treating hypernasal speech in children with infantile-onset Pompe disease - Zeng, Yin-Ting; Liu, Wen-Yu; Torng, Pao-Chuan; Hwu, Wuh-Liang; Lee, Ni-Chung; Lin, Chun-Yi; Chien, Yin-Hsiu (Scientific reports, 2021)
Children with infantile-onset Pompe disease (IOPD) demonstrate hypernasality. This study aimed to evaluate whether continuous positive airway pressure (CPAP) training may reduce hypernasality in children with IOPD. Five children with IOPD were enrolled in a single-subject experimental design of type A-B-A′. The intervention comprised an 8-week, 6-day-per-week regimen of CPAP training at home. Participants continued traditional speech therapy once per week throughout the 24-week study duration. The outcome measurements included the degree of hypernasality (DH), the percentage of consonants correct (PCC), and the speech intelligibility score (SIS). C-statistic analysis with an α of 0.05 was used along with visual analysis to assess speech changes. Three patients completed the study. During the CPAP training phase, the DH, PCC, and SIS were significantly improved compared with the baseline ( p < 0.05). At the follow-up phase, both DH and SIS were improved compared with the baseline ( p < 0.05), but the PCC had returned to the baseline level. CPAP training demonstrated effectiveness in reducing nasal sounds in IOPD patients. Further studies training younger children with normal hearing may help elucidate the persistence of the effects in children with IOPD.